STAGES OF PERSONAL CAREER GROWTH - Nilufar, Rakhimkorieva (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
This article discusses personal career growth, the most important ones related to personnel management, the goals of rational organization of career management, as well as career, the complexity of the work of employees or the role of work in the social hierarchy.